Analysis of Apriori Algorithm on Sales Transactions to Arrange Placement of Goods on Minimarket - Putu Bagus Indra Sukadiana Putra; Ni Putu Sri Merta Suryani; Sri Aryani (International Journal of Engineering and Emerging Technology, 2018)
In the business world, business development is a veryimportant factor to be reckoned with. This is done in order toalways survive in the competitive world of business. Improvingproduct quality, adding product types and reducing the company'soperating costs are some things that can be done in order tosurvive in the competition. The thing that can be done to meetthose needs is to perform sales transaction data analysis usingData Mining. One of the Algorithms that belongs to an associationin Data Mining that matches is the Apriori Algorithm. A priorialgorithm aims to find frequent item sets in a set of data. A priorialgorithm defined a process to find a priori rules that meetminimum requirements for support and minimum requirementsfor confidence. This research seeks to develop a business strategyof placement of groceries that is adjusted to the consumerconsumption pattern in minimarket. Thus, the arrangement ofmerchandise can be adjusted with the rules of association to fit thepattern of consumer consumption.